Facilitating educational opportunities and raised self-esteem in disadvantaged young people in South East Wales: Effects of the Junior Rock Music Academy widening participation programme. Issue 1 (1st April 2021) - Ellis, Jane
This study examined the effects of the Junior Rock Music Academy (JRMA) on participants' (N = 39) confidence and self-esteem. The JRMA was a widening participation Saturday music programme developed to reduce the influences of poverty on educational underachievement for young people (10‐18 years) from poorer families across South East Wales. Participants' confidence and self-esteem scores reported a significant rise, with no significant difference reported between genders or age groups. Participants (N = 5), programme tutors (N = 3) and participant parents/guardians (N = 4) were interviewed using semi-structured interviews to establish the fidelity of the structure and content of the intervention. The impact of JRMA on the psychosocial, cultural and emotional characteristics of participants and their parents/guardians as barriers to educational attainment and preparedness to thrive in education are discussed; these include enhanced cognitive development, social and emotional skills and learner motivation.